2016
DOI: 10.1007/s00294-016-0584-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the non-ribosomal peptide synthetase responsible for biosynthesis of the potential anti-cancer drug sansalvamide in Fusarium solani

Abstract: Sansalvamide is a cyclic pentadepsipeptide produced by Fusarium solani and has shown promising results as potential anti-cancer drug. The biosynthetic pathway has until now remained unidentified, but here we used an Agrobacterium tumefaciens-mediated transformation (ATMT) approach to generate knockout mutants of two candidate non-ribosomal peptide synthetases (NRPS29 and NRPS30). Comparative studies of secondary metabolites in the two deletion mutants and wild type confirmed the absence of sansalvamide in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…4, it is noted that all isolates showed a clear band of NRPS genes. Although Fusarium is known to bring NRPS and PKS genes in its genome naturally (Hansen et al 2012;Romans-Fuertes et al 2016), this is the first report of the discovery of NRPS genes in Eutypella and Lasiodiplodia. It should also be noted that only a few peptides are reported from these genera (Wei et al 2014).…”
Section: Discussionmentioning
confidence: 90%
“…4, it is noted that all isolates showed a clear band of NRPS genes. Although Fusarium is known to bring NRPS and PKS genes in its genome naturally (Hansen et al 2012;Romans-Fuertes et al 2016), this is the first report of the discovery of NRPS genes in Eutypella and Lasiodiplodia. It should also be noted that only a few peptides are reported from these genera (Wei et al 2014).…”
Section: Discussionmentioning
confidence: 90%
“…129 To use a hydroxy acid as a building block substrate, both (1) availability and (2) selection of such substrates must be addressed by the BGC. (1) α-hydroxy acids are not common in primary metabolism, so in fungal systems that use α-hydroxy acids as NRPS substrates, the BGC often contains standalone ketoreductase (KR) proteins which convert α-keto acids to α-hydroxy acids in an NADPH-dependent reduction reaction [130][131][132][133][134] (Figure 4), with keto acids arising from branched-chain amino acid biosynthesis pathways 135 or from glycolysis. These KR proteins are not closely related to PKS KR domains, 128,136,137 but belong to the ApbA_C superfamily, which includes ketopantoate reductases.…”
Section: Ester Bond Formation During Elongation By a C Domain In Nomentioning
confidence: 99%
“…Other depsipeptides for which ester bond formation occurs during elongation and is catalyzed by a C domain include the destruxins 131,132,142,143 and sansalvamide. 132 Destruxins are cyclic insecticidal molecules synthesized in fungal entomopathogens by a 6-module NRPS. 142 Module 2 is likely responsible for inserting the ester bond, starting with direct selection of the α-hydroxyisocaproic acid by the A domain.…”
Section: Ester Bond Formation During Elongation By a C Domain In Nomentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the biosynthesis of destruxins has been reported, and revealed that the macrocyclic structure of destruxins could be biosynthetically provided by macrolactamization after the nonribosomal peptide synthesis of a cyclization precursor. 30,31) Thus, the results of the above biosynthesis suggest that macrolactamization is an effective method for the formation of a macrocyclic structure in destruxin synthesis. On the other hand, solid-phase synthesis is a powerful method for preparing a combinatorial library toward the elucidation of structure-activity relationships.…”
Section: Reviewmentioning
confidence: 99%